Writing Ability of Paragraph Arguments of Students Who Have High Reading Interest in the Group Using the Quantum Writing Method - Ika Nurjanah; Biner Ambarita; Abdul Muin Sibuea (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study discusses about writing ability of paragraph arguments of students whose have high reading interest in the group using quantum writing method. The location of this study is MAS of Academic School of Islamic Education 2017/2018. The result shows that the ability to write paragraph arguments for students who are taught using higher quantum writing. The ability to write paragraphs in arguments for students with high reading interest is more suitable to be taught using the quantum writing method